Effects of Malarial Parasitaemia on Haematological Parameters and Gender Distribution in District Gamba, Gilgit-Baltistan - Alam, Mustajab; Khalid, Usama; Ahmed, Ali; Zia, Qasim; Ghawas, Ali (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the effects of malaria infection on haematological parameters, and to know common parasite species of malaria in Skardu region (Gilgit-Baltistan).Study Design: Cross-sectional study.Place and Duration of Study: Combined Military Hospital, Skardu Pakistan, from Jan to Dec 2022.Methodology: A group of 100 patients with various malaria symptoms, all of whom had tested positive for the disease, was enrolled. Written consent was obtained before enrolment, and their confidentiality was ensured at all levels. Blood smears were examined to identify and quantify malaria parasites, and a Sysmex XP 300 haematology analyser was used to measure haematological parameters. Several haematological parameters were studied in the infected participants, including WBCs, RBCs, platelets, Hb, haematocrit, MCV, MCH, neutrophil, and lymphocyte percentages. Descriptive statistics were presented as Mean±SD.Results: Out of total patients, 64% patients were male and 36% were female. Out of the total cases of malaria infection, 80% were diagnosed with Plasmodium vivax, 12% with Plasmodium falciparum, and 8% had a mixed infection. A stronger connection between Plasmodium vivax and thrombocytopenia, with a p-value of 0.020, was observed, whereas Plasmodium falciparum was more strongly associated with anaemia and leukopenia.Conclusions: Participants enrolled in the study who contracted malaria exhibited significant alterations in several blood-related characteristics. Among these, anaemia, thrombocytopenia, lymphopenia, monocytosis, and eosinopenia emerged as the key indicators of malaria infection, particularly in cases involving the Plasmodium falciparum species.